PSYCHOSOCIAL TRAFFIC AUTOPSY AS A STRATEGY FOR ASSESSING INTENTIONALITY IN ROAD TRAFFIC INCIDENTS: A METHODOLOGICAL STUDY - Cabral Filho, Francisco Williams; da Silva, Eudemberg Pinheiro; Palácio, Paulo Henrique Duarte; da Silva, Aaron Macena; Braga, Jennyfer Lara Pinheiro da Silva; de Souza, Larissa Rakel Rodrigues; Pereira, Shírley Moura; Uchoa, Maria Clara de Matos; Machado, Daniel Leite; Duarte, Rayane Ferreira; Macena, Raimunda Hermelinda Maia (Seven Editora, 2025)
Traffic accidents rank among the leading causes of death from external causes and constitute a major public health concern. Traditionally classified as unintentional events, these fatalities are often attributed to human error, environmental conditions, or deficiencies in road infrastructure. However, scientific evidence indicates that some of these deaths may involve signs of self-harm intentionality, which remain largely underreported and are frequently recorded as accidents of undetermined cause. In light of this gap, the present study aims to introduce traffic psychosocial autopsy as an innovative methodological strategy for assessing intentionality in fatal road accidents. This study is a methodological development, qualitative and applied in nature, which systematizes an integrated process for retrospective investigation of traffic-related deaths. The methodology adapts the principles of classical psychological and psychosocial autopsies, expanding them to incorporate technical-forensic, psychosocial, epidemiological, environmental, and institutional data. The process is organized into six sequential steps: case identification, integration of data sources, retrospective psychosocial investigation, technical and contextual road analysis, intersectoral integration and inference session, and preparation of a technical report with recommendations. It is concluded that the traffic psychosocial autopsy enhances the analytical capacity of traffic death investigations, contributes to improving epidemiological surveillance, and supports intersectoral public policies aimed at preventing avoidable fatalities. DOI: https://doi.org/10.56238/sevened2025.036-140